Particulate Matter in the American Southwest: Detection and Analysis of Dust Storms Using Surface Measurements and Ground-Based LIDAR - Joscelyne Guzman-Gonzalez; Rosa M. Fitzgerald; Nakul N. Karle; Ricardo K. Sakai; William R. Stockwell (Atmosphere, 2024)
This research study focuses on the coupling between particulate matter and the planetary boundary layer. Particulate matter affects human health and it is a complex mixture of suspended substances. Various sources of particulate matter include volcanic eruptions, soil lofted by strong winds, wildfires, and particles formed from chemical reactions of gas-phase emissions. Strong winds are one source of dust pollution when they loft soil particles. Particulate matter and the planetary boundary layer are closely linked. The planetary boundary layer plays a critical role in meteorology and particulate matter concentrations due to its involvement in energy, latent heat, and mass transfer with the free troposphere. Currently, there has been no research on the impact of dust events on the planetary boundary layer in our region, El Paso, Texas, which is located on one of the biggest sources of dust in the Western Hemisphere, the Chihuahuan Desert. In this study, we used PM10 concentrations to detect dust events during the 2016–2022 period in the El Paso region. During the study period, we observed 74 dust events. The dust events were categorized as synoptic or convective cases. Synoptic cases are associated with cold fronts, while convective cases are associated with local convective systems such as thunderstorms. We observed that synoptic cases occurred most frequently during springtime, while convective cases were more frequent during summer monsoon months. Synoptic cases tend to occur earlier in the afternoon with lower temperatures, while convective cases tend to occur in the late evening with higher temperatures. We also found that the planetary boundary layer height collapsed after the maximum hourly PM10 concentration and then the boundary layer returned to its original height.